Lessons from Foreign Owned Spaza Shops in South African Townships - Lamb, Byron; Kunene, Lindiwe Nqobile; Dyili, Nomalizo Florence (Journal of Reviews on Global Economics, 2019)
In 2014, the World Bank pronounced how the informal sector is probably responsible for half of the GDP in developing countries. This sector can no longer be ignored as it is embedded in most developing countries’ economies. In a country like South Africa, the informal sector is a gateway to economic freedom where the historically deprived groups were left behind and could not participate in the formal economic sectors, as they would have liked. This was due to racially skewed policies of the apartheid regime. The country saw black racial groups marginalised from acquiring appropriate skills, education and resources to allow them to participate in the formal economy. The barrier to entry into formal economies resulted in the significant rise of the informal economy. One of the most prevalent business forms in this sector has been Spaza Shops. In fact, in South Africa, Spaza Shops have become synonymous with the informal sector. Post-apartheid, with the opening of the country’s borders over the years, there has been an increase in foreign owned Spaza Shops both legally and illegally, at the expense of locally owned ones. Using an exploratory research design, this paper sought to uncover various practices and procedures that have been accredited to the success of foreign owned Spaza’s in townships. Through qualitative engagement with relevant literature published over a period of six years, a relationship between foreign owned businesses and locally owned businesses in the townships of South Africa was investigated. The study outcomes identified motives for increased and successful foreign owned businesses in townships. These are Networking and Economies of Scales; Socio-Economic Motivators; Geographic Location; Financial Management, Entrepreneurial Orientation and Business practice. All of these motives are seen as equally important and can be used to upskill and motivate local informal traders to be as competitive within the township economy.